(untitled) (Medical Forum Monthly, 2024)
Objective; This study was conducted to see the parental feedback regarding the prevalence of asthma symptoms in their children. Study Design: A cross sectional study. Place and Duration of Study: This study was conducted in a local school from December 2012 to March 2013. Materials and Methods; This is a questionnaire based descriptive cross-sectional study. We selected a local school in which there are around 500 students. Results: We had 238 questionnaires back out of 500, showing response rate of 47.6%. We found that 38 students had asthma, almost 16%, and there was male predominance. Night cough was the most common complaint in these students. Parental asthma was noted in 18% of the asthmatics. Conclusion; This questionnaire based study revealed asthma to be more common in this part of Pakistan. More studies are required to see the validity of the observation. Asthma being more common and an important health concern, requires prompt health education of the public and health professionals as well as further research work.